An Introduction to the science of deception and lie detection - Street, Chris N. H. (Routledge, 2023)
* A comprehensive guide to the science of deception and its detection. * Covers the latest updates in the field, such as current lie-detection theories and research into unconscious lie detection. * Highlights the role of theoretical developments for our understanding of deception. * Written to be accessible to students of all levels on cognitive, forensic, and investigative psychology courses. * Each chapter includes excercise solutions to aid instruction and facilitate learning. * Synthesises the theoretical approaches to understanding human lie detection